Network Pharmacology and In Vitro Experimental Verification Reveal the Mechanism of the Hirudin in Suppressing Myocardial Hypertrophy - Liu, Mengnan; Luo, Gang; Dong, Li; Mazhar, Maryam; Wang, Li; He, Wenlu; Liu, Yan; Wu, Qibiao; Zhou, Hua; Yang, Sijin (Frontiers in Pharmacology, 2022)
Background: Myocardial hypertrophy is a complex pathological process, which is a common manifestation during the development of various cardiovascular diseases. Hirudin has been shown to have therapeutic effects on a variety of cardiovascular diseases, however, its therapeutic effect on myocardial hypertrophy is still unknown, and its chemical and pharmacological characteristics remain to be elucidated. Methods: In this study, the network pharmacology method was used to characterize the mechanism of hirudin on myocardial hypertrophy. The potential protein targets of hirudin and myocardial hypertrophy were both obtained from the Genecards database, and potential pathways associated with genes were identified by Gene Ontology and pathway enrichment analysis, and the data were displayed in a visual manner. Subsequently, the potential mechanism of action of hirudin on myocardial hypertrophy predicted by network pharmacology analysis was verified by molecular docking, and finally, the main findings were further verified by in vitro experiments by molecular biology techniques. Results: A total of 250 targets of hirudin, and 5376 targets related to myocardial hypertrophy after deduplication were collected. The drug-disease network showed the relationship between hirudin, myocardial hypertrophy, and the targets. Further, systematic analysis from the PPI network indicated that blood coagulation, vesicle lumen, and signaling receptor activator activity may be the potential mechanisms of hirudin in the treatment of myocardial hypertrophy, and the PI3K/AKT signaling pathway may be the most relevant to the therapeutic effect of hirudin. Then, three therapeutic targets that were highly related to myocardial hypertrophy were extracted. Hirudin can be highly bound to STAT3, IL-6, and MAPK1 and found by molecular docking, which may be the basis for its inhibitory effect on myocardial hypertrophy. In addition, in vitro experiments showed that hirudin could inhibit AngII-induced hypertrophy and death of H9c2 cells, and significantly reduce the mRNA and protein expression levels of STAT3, MAPK1, and IL-6.